Insight into the Lubrication and Adhesion Properties of Hyaluronan for Ocular Drug Delivery - Černohlávek, Mikuláš; Brandejsová, Martina; Štěpán, Petr; Vágnerová, Hana; Hermannová, Martina; Kopecká, Kateřina; Kulhánek, Jaromír; Nečas, David; Vrbka, Martin; Velebný, Vladimír; Angeles, Gloria Huerta (MDPI, 2021)
Hyaluronan (HA) is widely used for eye drops as lubricant to counteract dry eye disease. High and low molecular weight HA are currently used in ophthalmology. However, a large portion of the current literature on friction and lubrication addresses articular (joint) cartilage. Therefore, eye drops compositions based on HA and its derivatized forms are extensively characterized providing data on the tribological and mucoadhesive properties. The physiochemical properties are investigated in buffers used commonly in eye drops formulations. The tribological investigation reveals that amphiphilic HA-C12 decreases the friction coefficient. At the same time, the combination of trehalose/HA or HAC12 enhances up to eighty-fold the mucoadhesiveness. Thus, it is predicted a prolonged residence time on the surface of the eye. The incorporation of trehalose enhances the protection of human keratinocytes (HaCaT) cells, as demonstrated in an in-vitro cell-desiccation model. The presence of trehalose increases the friction coefficient. Medium molecular weight HA shows significantly lower friction coefficient than high molecular weight HA. This research represents a first, wide array of features of diverse HA forms for eye drops contributing to increase the knowledge of these preparations. The results here presented also provide valuable information for the design of highly performing HA-formulations addressing specific needs before preclinic.

Hyaluronan (HA) is widely used for eye drops as lubricant to counteract dry eye disease. High and low molecular weight HA are currently used in ophthalmology. However, a large portion of the current literature on friction and lubrication addresses articular (joint) cartilage. Therefore, eye drops compositions based on HA and its derivatized forms are extensively characterized providing data on the tribological and mucoadhesive properties. The physiochemical properties are investigated in buffers used commonly in eye drops formulations. The tribological investigation reveals that amphiphilic HA-C12 decreases the friction coefficient. At the same time, the combination of trehalose/HA or HAC12 enhances up to eighty-fold the mucoadhesiveness. Thus, it is predicted a prolonged residence time on the surface of the eye. The incorporation of trehalose enhances the protection of human keratinocytes (HaCaT) cells, as demonstrated in an in-vitro cell-desiccation model. The presence of trehalose increases the friction coefficient. Medium molecular weight HA shows significantly lower friction coefficient than high molecular weight HA. This research represents a first, wide array of features of diverse HA forms for eye drops contributing to increase the knowledge of these preparations. The results here presented also provide valuable information for the design of highly performing HA-formulations addressing specific needs before preclinic.
Insight into the Lubrication and Adhesion Properties of Hyaluronan for Ocular Drug Delivery
Keywords: hyaluronan; biotribology; friction; lubrication; eye drops; hyaluronan; biotribology; friction; lubrication; eye drops